2004
DOI: 10.1051/0004-6361:20041136
|View full text |Cite
|
Sign up to set email alerts
|

C, S, Zn and Cu abundances in planet-harbouring stars

Abstract: Abstract. We present a detailed and uniform study of C, S, Zn and Cu abundances in a large set of planet host stars, as well as in a homogeneous comparison sample of solar-type dwarfs with no known planetary-mass companions. Carbon abundances were derived by EW measurement of two C  optical lines, while spectral syntheses were performed for S, Zn and Cu. We investigated possible differences in the behaviours of the volatiles C, S and Zn and in the refractory Cu in targets with and without known planets in ord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 38 publications
9
100
6
Order By: Relevance
“…Our [C/Fe] determinations for dwarfs are somewhat lower than in other works (Ecuvillon et al 2004b;Gonzalez & Laws 2000;Reddy et al 2003). We found that the Sun is slightly overabundant in carbon compared to other dwarfs in the same metallicity range, which is the opposite situation found by those A71, page 6 of 13 authors.…”
Section: Resultscontrasting
confidence: 83%
“…Our [C/Fe] determinations for dwarfs are somewhat lower than in other works (Ecuvillon et al 2004b;Gonzalez & Laws 2000;Reddy et al 2003). We found that the Sun is slightly overabundant in carbon compared to other dwarfs in the same metallicity range, which is the opposite situation found by those A71, page 6 of 13 authors.…”
Section: Resultscontrasting
confidence: 83%
“…τ Boo was noted as a metal-rich star according to the criterion [Fe/H] > 0.2. Subsequently, the high metallicity of our target was confirmed by several accurate abundance analyses, the most recent performed by Ecuvillon et al (2004b), Valenti & Fischer (2005), Takeda & Honda (2005), Gilli et al (2006), Luck &Heiter (2006), andTakeda (2007).…”
Section: Photospheric Abundancesmentioning
confidence: 56%
“…The final set of abundances, together with the number of element lines used to derive the abundances and respective errors (denoting the error on the mean) are listed in Table 3. Moreover, we also derived abundances of several volatile elements (C, O, S, and Zn) and heavier elements, following the procedures of Ecuvillon et al (2004) and Bertran de Lis et al (2015). The values allow us to conclude that HD 219828 is a typical thin-disk star from the solar neighbourhood; its [α/Fe] 6 abundance ratios are nearly solar (i.e.…”
Section: Hd 219828: the Starmentioning
confidence: 99%